Upside down in the middle of nowhere - Lamana, Julie T. (San Francisco : Scholastic, 2014)
At the end of August 2005, ten-year-old Armani is looking forward to her birthday party in the Lower Ninth Ward of New Orleans, where she and her extended family live, but Hurricane Katrina is on the way, bringing destruction and tragedy in its wake.
R
750
R
Keywords: Hurricane Katrina, 2005 -- Juvenile fiction; African American families -- Louisiana -- New Orleans -- Juvenile fiction; Survival -- Louisiana -- New Orleans -- Juvenile fiction; Hurricane Katrina, 2005 -- Fiction; African Americans -- Fiction; Family life -- Louisiana -- Fiction; Survival -- Fiction; Lower Ninth Ward (New Orleans, La.) -- Juvenile fiction; New Orleans (La.) -- Juvenile fiction; New Orleans (La.) -- Fiction